2017
DOI: 10.5005/jp-journals-10015-1441
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude toward Orthodontic Treatment among treated Subjects compared with Untreated Subjects and Correlation with Patient—Orthodontist Communication

Abstract: Aim: This study was designed to evaluate knowledge and awareness toward orthodontic treatment among treated subjects as compared with untreated subjects and to correlate the communications between treated subjects and their practicing orthodontists. Materials and methods:Self-reported questionnaires were distributed to be completed by the consent subjects. They were 340 untreated subjects (220 males and 120 females) and 102 subjects (57 males and 45 females) who recently received orthodontic treatment in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…[9] This might contribute to the improved oral hygiene behavior observed among many orthodontic patients. [10,11] Nonetheless, supporting preventive oral hygiene measures through long-term treatment necessitates patient compliance. Unfortunately, several studies have demonstrated poor oral hygiene compliance among orthodontic patients [12][13][14] with a rapid drop in patients' compliance after bonding the orthodontic appliance.…”
Section: Introductionmentioning
confidence: 99%
“…[9] This might contribute to the improved oral hygiene behavior observed among many orthodontic patients. [10,11] Nonetheless, supporting preventive oral hygiene measures through long-term treatment necessitates patient compliance. Unfortunately, several studies have demonstrated poor oral hygiene compliance among orthodontic patients [12][13][14] with a rapid drop in patients' compliance after bonding the orthodontic appliance.…”
Section: Introductionmentioning
confidence: 99%